Право журналіста на нерозкриття джерел інформації - Стрєльцова, Анастасія (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
Access to information is one of the important factors of a journalist’s work. The effective professional activity of a journalist is impossible without alternative sources of information and the opportunity to use them, since truthful coverage of socially significant issues by journalists is a necessary sign of the existence of a democratic society. However, it is worth noting that often socially significant information is hidden and thanks to the sources of information it can be published and brought to the general public. The right to keep the person who provided the information confidential is the exclusive right that journalists have and other citizens do not have.